Beyond Bear's Paw : the Nez Perce Indians in Canada - Greene, Jerome A. (University of Oklahoma Press, 2010)
"In the fall of 1877, Nez Perce (Nimiipuu) Indians were desperately fleeing U.S. Army troops. After a 1,700-mile journey across Idaho, Wyoming, and Montana, the Nez Perces headed for the Canadian border, hoping to find refuge in the land of the White Mother, Queen Victoria. But the army caught up with them at the Bear's Paw Mountains in northern Montana, and following a devastating battle, Chief Joseph and most of his people surrendered." "The tale of Chief Joseph and his followers is now legendary, but Bear's Paw is not the entire story. In fact, nearly three hundred Nez Perces escaped the U.S. Army and fled into Canada. Beyond Bear's Paw is the first book to explore the fate of these "nontreaty" Indians. Drawing on hitherto unexplored Canadian and U.S. sources, including reminiscences of Nez Perce participants, Jerome A. Greene presents an epic story of human endurance under duress." "Greene describes the tortuous journey of the small band who managed to elude Colonel Nelson A. Miles's command. After the escapees crossed the "Medicine Line" into the British Possessions, they found only new trauma. Within a few years, most of them stole back to their homelands in Idaho Territory. Those who remained north of the line faced a difficult and uncertain future." "In recent years, Nimiipuu descendants from the United States and Canada have revisited their common past and sought reconciliation. Beyond Bear's Paw offers new perspectives on the Nez Perces' struggle for freedom, their hapless rejection, and their ultimate cultural renewal."--BOOK JACKET.